Islamic engineering ethics: foundation integration and practice - Shuriye, Abdi Omar (Future Text Publications, 2006)
Most values and ethical principles are universal; however, the motives to adapt these values are cultural dependent. Thus it became important to equip muslim engineers with the origin of professional ethical principles in Islam. In fact, Islam provides general guidelines for some contemporary issues such as environmental protection, privacy intrusion and priorities in risk analysis. In view of the enormous early Muslim contributions to the world civilizations, there is a need to reexamine the Islamic heritage in order to contextualized these contributions. Although various works have been written on the subject, practical steps are needed to translate the theory into implementable methodology. It is with this intention that this book is produced.